University Entrepreneurship and Professor Privilege - Erika Färnstrand Damsgaard; Marie Thursby (Research Institute of Industrial Economics (IFN), 2012)
This paper analyzes how institutional differences affect university entrepreneurship. We focus on ownership of faculty inventions, and compare two institutional regimes; the US and Sweden. In the US, the Bayh-Dole Act gives universities the right to own inventions from publicly funded research,whereas in Sweden, the professor privilege gives the university faculty this right. We develop a theoretical model and examine the effects of institutional differences on modes of commercialization; entrepreneurship or licenses to established firms, as well as on probabilities of successful commercialization. We find that the US system is less conducive to entrepreneurship than the Swedish system if established firms have some advantage over faculty startups, and that on average the probability of successful commercialization is somewhat higher in the US. We also use the model to perform four policy experiments as suggested by recent policy debates in both countries.
Keywords: L24; L26; O31; O38; 330; Entrepreneurship; Professor privilege; Commercialization; Startup; Hochschulforschung; Hochschullehrer; Innovation; Kommerzialisierung; Unternehmer; Hochschulrecht; Schweden; USA